Carbon nanotubes: the challenges of the first syntheses trials - Coelho, C. A. (2015)
Carbon nanotabes (ONT), due to their unique properties:, are suitable for application in biomedical devices. However these devices are not available in the market because of problems associated It biocompatibility and synthesis reproducibililty. Indeed, the production of vertically it boa nanotubes (VA-CNTs) is needed for most of these applications. The most common synthesis method, Chemical Vapor Deposition (CVD), involves a large number of parameters, not all known, and their influence on the process is not fully understood.. Knowing that the synthesis of CNTs is performed in a variety of lab conditions and in different durnace systems, which makes it impossible to create a universal recipe for use in all labs, this paper aims to start the design of an universal protocol that all labs can use to generate a suitable recipe for their environmental conditions and furnace system. The influence of parameters such as best deposition spot. and tube bakintz was assessed. During this evaluation, the importance cth other factors (catalyst uniformity and climacteric conditions) to the pmcess has been revealed. The universal pmtocol suggested is in an cat: stage and needs to be improved.